Pengembangan Media Pembelajaran Berbasis Android Pada Mata Kuliah Fisika Dasar - Novi Hendri Adi; Atman Lucky Fernandes; Hermansyah Hermansyah (Cetta: Jurnal Ilmu Pendidikan, 2020)
The aim of the research is to develop an Android-based learning media on basic physics courses in informatics engineering at STT Ibnu Sina which is valid, practical, effective. This study uses a method with Four-D design applied to develop and test the validity, practicality and effectiveness of android-based learning media. The stages of the research include defining, designing, developing, and distributing. The results of testing the validity of Android-based learning media indicate that the learning media are valid. Based on the response of lecturers and students about the practicality of instructional media shows that learning media is very practical and based on student learning outcomes indicate that the Android-based learning media has been effectively used in basic physics learning. The results of data analysis show that Android-based learning media is better in improving student learning in the basic physics learning process. Then concluded that the Android-based learning media can be applied in learning basic physics. Android-based learning media can be developed more broadly along with technological developments in the learning process.